Genotyping of MC4R gene (G923>T) and its association with productive performance and carcass traits in Ross 308 - Alaa Mohammad-faeq Mohammad-Ameen, Alaa Mohammad-faeq Mohammad-Ameen; Eman Hasan AL-Anbari, Eman Hasan AL-Anbari (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2026)
This study was aimed to select MC4R gene as a candidate gene for growth and carcass traits in Ross 308. The productive characteristics were studied weekly for 42 days for 100 chicks numbered individually. Blood samples were collected from chickens at 21 days old, Genotypes of MC4R were obtained using PCR products sequence. In this study, DNA sequencing data for the MC4R gene was detected technique SNP(G923>T) (1050bp) with three genotype appeared as (GG- GT- TT). However, the results show that a highly significant differences (P<0.01) between the MC4R genotype and body weight, weight gain, leg length and drumstick weight, with a significantly differences (P<0.05) in all of breast depth, drumstick length, carcass weight, back weight, weight of wings and abdominal fat weight. There was no variation detected in body length, breast circumference, drumstick circumference, breast, Neck, Liver, Heart and Gizzard weight. The MC4R gene SNP (G923>T) could be considered as a candidate marker gene for the early chicken selection program for growth and some carcass traits. The abstract must be no longer than 250 words and must clearly emphasise the objective of the study.